3-D SPHERICAL MODELS FOR MANTLE CONVECTION, CONTINENTAL DRIFT, AND THE FORMATION AND DISINTEGRATION OF SUPERCONTINENTS - Trubitsyn V.P.; Rykov V.V. (My University, 1998)
One of the most important problems of geoscience is to explain the drift mechanism of continents uniting periodically to form supercontinents similar to Pangea. This work presents for the first time a numerical model of mantle convection in a 3-D spherical mantle with drifting continents. The mantle is modeled by a viscous fluid developing thermal convection upon heating. When the floating continents are placed into the mantle, they start drifting under the effect of the forces of viscous coupling with mantle convection flows. Subject to numerical solution is the set of mass, heat, and momentum transfer equations for convection in the viscous mantle and the associated set of Euler equations for the movement of each solid continents. The mantle and continents interact with each another mechanically in the course of heat exchange. In order to better understand the mantle-continent interaction processes, we have analyzed two models, one with a single continent and a weak thermal convection with a Rayleigh number of 10 4 and the other with five continents and an intense thermal convection with a Rayleigh number of 10 6. In case of the weak convection, there are formed in the mantle a few ascending and descending flows. The drifting continent is pulled into one of the descending flows. As the size and shape of the continent differ from those of the descending flow zones, its position proves unstable, so that it drifts constantly. In the absence of other continents and any external forces, the continent moves along the descending flow system. At higher Rayleigh numbers, the convection becomes nonstationary, in which case the number, shape, and position of mantle convection flows vary constantly. Besides is more, if there are several continents, the motion of each of them becomes bound and more complex. The continents can collide directly, as well as interact with each other through the intermediary of the mantle and thus change the structure of its convection. The numerical experiments performed demonstrate the possibility of both a partial uniting of several continents and the formation of a single supercontinent like Pangea upon the uniting of all the continents.
Keywords: MANTLE CONVECTION; FLOATING CONTINENT; NUMERICAL SIMULATION; EVOLUTION OF THE MANTLE-CONTINENT SYSTEM; 3D MODELS